PLACE AND ROLE OF AGENCY FOR FINANCING RURAL INVESTMENTS - AFIR IN ABSORBING EUROPEAN FUNDS - Sebastian GUT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyses the activity of the Agency for Financing Rural Investments (Agenția pentru Finanțarea Investițiilor Rurale - AFIR) in order to ensure the process of informing and implementing on how to access European funds granted through the National Rural Development Plan (NRDP) for the period of 2014-2020, following the types of measures and submeasures, the amounts granted and the advantages obtained through their accession by the applicants as a result of the agreements existent between the European Community and Romania. The actions of AFIR, through its central, regional and county representatives, are aimed at informing and communicating, according to the Regulation on Organization and Functioning of the Agency for Financing Rural Investments and the Manual of Procedures for Public Relations, for knowledge transfer in view of increasing the competiveness and diversification in agriculture, and for the need to modernize the agricultural sector by processing and marketing of agricultural products and by market development, ensuring a wide range of products and services together with the use of renewable energy in order to protect the environment. The methodology used consists in studying the references, collecting, processing, analysing and interpreting the data provided by the databases of AFIR and the Ministry of Agriculture and Rural Development (MARD), as well as formulating conclusions on the situation of the submitted projects, allocated amounts, achieved targets and measures to be further taken in support of rural areas.